ASUHAN KEBIDANAN BERKELANJUTAN DARI KEHAMILAN HINGGA KELUARGA BERENCANA DI PRAKTIK MANDIRI BIDAN: LAPORAN KASUS: CONTINUITY OF MIDWIFERY CARE FROM PREGNANCY TO FAMILY PLANNING IN INDEPENDENT MIDWIFERY PRACTICE: A CASE REPORT - Winarti, Sri; Purwanti, Yanik (WELL BEING, 2025)
Continuity of Care (COC) is an integrated service approach aimed at improving maternal and infant health from pregnancy through family planning. This case study aims to describe the implementation of COC for Mrs. D at PMB Sri Winarti. The method used was qualitative with a comprehensive case study approach, covering third trimester pregnancy care, childbirth, newborn care, postpartum care, and contraception. The results showed that all stages of care took place physiologically without complications. Antenatal examination showed a hemoglobin level of 12 g/dl, reflecting good nutritional status. The mother experienced mild edema in the lower extremities, but normal blood pressure and a negative urine reduction test, thus not indicating preeclampsia. The delivery process was spontaneous and safe, the baby was born healthy and Early Initiation of Breastfeeding was carried out. During the postpartum period, minor complaints were overcome through self-care education and breathing relaxation. At the end of the postpartum period, the mother chose a three-monthly injectable contraceptive that is safe for breastfeeding mothers. It was concluded that the implementation of Continuity of Care was running optimally and had a positive impact on the well-being of the mother and baby and the quality of midwifery services.